Evaluation of cytokine response to extracorporeal membrane oxygenation. Issue 1 (18th October 2021) - Liu, Tom; Amos, Shayna H.; Ganga, Anil L.; Bullins, Charles M.; Jennings, Cathy D.; Arnold, W. Scott; Joseph, Mark
Abstract: Rationale: Increased cytokine response is common in patients receiving extracorporeal life support and is often a poor prognostic indicator. There is interest in using adjunctive cytokine adsorption technologies to reduce inflammatory burden, However, it is debated whether extracorporeal membrane oxygenation (ECMO) itself provides therapeutic benefit beyond gas exchange. Thus, we sought to characterize the inflammatory profile of ECMO in the first 72–96 h of and quantify its effect on cytokine levels in a case series of patients undergoing ECMO. Methods: Eight patients initiating ECMO were studied. Of these, we measured cytokines pre‐ and post‐oxygenator over 96 h. Comparisons of cytokine levels were made across the oxygenator and over time. Results: The average age of patients was 64.3 years with 62% being male. Centrally cannulated patients had higher IL‐6 levels (820.43 vs. 6907.53 pg/ml, p  < 0.03), whereas peripherally cannulated patients had higher IL‐12p70 levels (7.73 vs. 2.59 pg/ml, p  < 0.05). Cytokine levels on day one included IL‐12p70 (4.17 ± 2.56), IL‐6 (4971.23 ± 8569.88), TNF (undetected), IL‐8 (346.68 ± 670.18), IL‐1B (undetected), and IL‐10 (72.27 ± 87.9). Cytokine levels increased over 96 h; however, no significant differences were appreciated despite blood product transfusion. On day 3, IL‐12p70 levels were significantly lower post‐oxygenator ( p  < 0.05). Conclusion: The inflammatory profile of ECMO does not change significantly over the early course of illness when accounting for transfusion. However, the decrease in IL‐12p70 specifically at day 3 of ECMO may indicate adsorption of specific inflammatory markers by the oxygenator although the clinical significance of this is still unknown. Further investigation of the oxygenator on cytokine response is warranted. Abstract : Proportion change of biomarkers due to the ECMO oxygenator by day.